Comparative Education of Wiktor Rabczuk (1931–2020): From the Study of Education in African Countries to European Education - Włoch, Anna (Acta Universitatis Nicolai Copernici. Pedagogika, 2023)
Wiktor Rabczuk was a well-known and respected researcher in Polish comparative education. A specialist in comparative research in the field of educational systems of African countries and Western European countries and a promoter of the “European dimension in education” in Polish schools, Rabczuk emerged from the field of comparative education, which was initially established by Bogdan Nawroczyński. Nawroczyński’s contributions in this field were subsequently continued by his student, Anna Mońka-Stanikowa. It was under her supervision that Rabczuk wrote and defended his doctoral thesis in comparative education. Like Mońka-Stanikowa, Rabczuk researched education in Western European countries, becoming an expert on private education and the educational policy of the European Union. This article aims to introduce Professor Wiktor Rabczuk and present his contribution to the development of Polish comparative education, especially during the period of Poland’s accession to the European Union. Although Rabczuk’s publications, which depict the challenges of education in European countries, remain essential for readers interested in these issues under analysis, no comprehensive study has been conducted on his achievements and scientific profile (apart from short biographies in the dictionaries of educators). The first part of this article presents an overview of Rabczuk’s biography, which is crucial to understanding the development of his research interests. The next part of the article presents Rabczuk’s achievements in the field of comparative education. A combination of content analysis of Rabczuk’s publications and an assessment of archival records have been presented in this article. The collected research material presents Rabczuk as the leading educational comparativist in Poland during the late 20th and early 21st centuries.